Developing Student’s German Language Competencies through Pragmatic Approach in the Classroom for Higher Education - Rina Evianty; Risnovita Sari; Muhammad Reza (BIRCU, 2020)
The general goal of teaching German as a foreign language is that learners can communicate appropriately in writing and orally in German. But in fact this goal can often not be achieved. Many learners in higher education master the German grammar and vocabulary, but they are unable to use German language that matches the social context, because they do not have much pragmatics competence. Pragmatic approach based on the function of language as a communication tool is a study of language by involving various aspects outside the language that are able to provide meaning. Pragmatic competence constitutes a significant factor in determining the success of communication. In fact, a German language learner in higher education is not only expected to use language and produce utterances which are understandable or grammatically correct, but is also expected to produce utterances which are socioculturally appropriate. However, for students in higher education who learn German as a Foreign Language (Deutsch als Fremdsprache/DaF), the pragmatic competence, which can actually be acquired naturally through social interaction, is quite difficult to acquire due to the limited. On this basis, pragmatics needs to be integrated into German language courses in higher education, which includes pragma linguistics and socio pragmatic. In this regard, this study describes not only the relationship between pragmatics and German as a foreign language, but also this study is an attempt to define its implications in teaching German as foreign language in higher education.